Apixaban decreases coagulation activity in patients with acute deep-vein thrombosis - Barrett, Yu Chen; Wang, Jessie; Knabb, Robert; Mohan, Puneet (Thrombosis and Haemostasis, 2011)
In patients with acute deep-vein thrombosis (DVT), apixaban, a direct oral factor Xa inhibitor, showed efficacy and safety similar to low-molecular-weight heparin followed by vitamin K antagonist (LMWH/VKA). We evaluated biomarkers of coagulation activity in relation to treatment dose, duration and clinical outcome. Patients (N = 520) with symptomatic DVT were randomised to receive apixaban (5 mg bid, 10 mg bid or 20 mg qd) or LMWH/VKA for 12 weeks. Plasma D-dimer, prothrombin fragment 1+2 (F1+2) and thrombin-antithrombin complex (TAT) levels were measured at baseline, and weeks 3 and 12 after treatment. Median plasma levels of D-dimer, F1+2 and TAT were elevated at baseline. At weeks 3 and 12, biomarker levels were normalised in most patients in all treatment groups, consistent with the low rate of venous thromboembolism (VTE) observed. Median reduction in D-dimer was similar in all treatment groups; percentage of patients with D-dimer above upper limit of normal decreased from 95% to 24–40% at week 12. F1+2 decline was greater with LMWH/VKA than apixaban. F1+2 in the apixaban groups changed to a similar extent (>84% of patients had F1+2 within reference range at week 12). Magnitude of TAT reduction was not quantifiable. In conclusion, levels of coagulation biomarkers decreased over 12 weeks of treatment with apixaban or LMWH/VKA in most patients with acute VTE. Baseline D-dimer and F1+2 were higher in patients with recurrent symptomatic VTE than in those without. Plasma levels of coagulation biomarkers did not appear to correlate with total bleeding events.
Keywords: Apixaban; blood coagulation; biomarkers; deep vein thrombosis; direct factor Xa inhibitor; oral anticoagulant